Optimization of the preparation process of vinblastine sulfate (VBLS)-loaded folate-conjugated bovine serum albumin (BSA) nanoparticles for tumor-targeted drug delivery using response surface methodology (RSM) - Yuangang Zu (Dove Medical Press, 2009)
Yuangang Zu, Yu Zhang, Xiuhua Zhao, Qi Zhang, Yang Liu, Ru JiangKey Laboratory of Forest Plant Ecology, Northeast Forestry University, Ministry of Education, Harbin, Heilongjiang, ChinaAbstract: Response surface methodology (RSM) was used to optimize the process of preparing bovine serum albumin (BSA) nanoparticles by desolvation, then the resulting BSA nanoparticles (BSANPs) were conjugated with folate to produce a drug carrier system that can specifically target tumors. The anticancer drug, vinblastine sulfate (VBLS), was loaded to this tumor-specific drug carrier system for the purpose of overcoming the nonspecific targeting characteristics and side effects of the drug. A central composite design was applied for modeling the process, which was composed of four independent variables, namely BSA concentration, the rate of adding ethanol (ethanol rate), ethanol amount, and the degree of crosslinking. The mean particle size and residual amino groups of the BSANPs were chosen as response variables. The interactive effects of the four independent variables on the response variables were studied. The characteristics of the nanoparticles; such as amount of folate conjugation, drug entrapment efficiency, drug-loading efficiency, surface morphology and release kinetics in vitro were investigated. Optimum conditions for preparing desired BSANPs, with a mean particle size of 156.6 nm and residual amino groups of 668.973 nM/mg, were obtained. The resulting folate-conjugated BSANPs (FA-BSANPs) showed a drug entrapment efficiency of 84.83% and drug-loading efficiency of 42.37%, respectively, and the amount of folate conjugation was 383.996 µM/g BSANPs. The results of this study indicate that using FA-BSANPs as a drug carrier system could be effective in targeting VBLS-sensitive tumors in the future.Keywords: bovine serum albumin, vinblastine sulfate, folate, targeted drug delivery, nanoparticles, response surface methodology